Peran PT Bank Pembiayaan Rakyat Syariah (BPRS) Amanh Bangsa Dalam Penyaluran Kredit Kepada Pengusaha Kecil di Sidamanik - Maulana Abdul Malik Tambunan; Ahmad Perdana Indra (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This study describes the role of BPRS in the development and strengthening of the community's economy. The purpose of this study, among others, is to determine the role of BPRS in developing MSMEs in Palopo City and to determine the impact felt by MSME actors in Sidamanik in the BPRS empowerment program. This survey is a field survey with a qualitative survey design and data collection using observation, interview, and documentation techniques. Keywords: Role, PT. BPRS Bank, Empowerment.